Pc3-4 ULF waves observed by the SuperDARN TIGER radar - Ponomarenko, P. V.; Menk, F. W.; Waters, C. L.; Sciffer, M. D. (HAL CCSD, 2005)
International audience Despite extensive research, the mechanisms for propagation of Pc3-4 energy from the generation region at the bow shock to the high-latitude ionosphere remain unresolved. We used high temporal (6-12s) and spatial (45km) resolution data from the SuperDARN TIGER radar (Tasmania) to examine Pc3-4 wave signatures at the F-region heights. We focus on a case study on 28 September 2000, when large-amplitude band-limited Pc3-4 oscillations were observed across 10-20 range gates in beam #4 (which points towards the CGM pole) for about four hours preceding MLT noon. These waves were detected in sea-scatter echoes reflected from the ionospheric footprint of the plasmatrough. Nearby ground magnetometer data from Macquarie Island showed very similar variations in both the north-south and east-west components. The radar data revealed the occasional presence of quasi-FLR (field-line resonance) spatial structures with frequencies much higher than those of the local fundamental FLR modes. Detailed spectral analysis of the ionospheric and ground data shows that these structures most probably correspond to a 3rd-harmonic, poloidal-mode FLR. Such observations suggest that compressional Pc3-4 waves produced in the upstream solar wind travel earthward from the magnetopause in the magnetic equatorial plane depositing energy into the Alfvenic modes, as either forced or 3rd-harmonic FLR that reach ionospheric heights along magnetic field lines.